EZH2 expression is a prognostic factor in childhood intracranial ependymoma: A Canadian Pediatric Brain Tumor Consortium study. Issue 9 (13th January 2015) - Li, Amanda M.; Dunham, Christopher; Tabori, Uri; Carret, Anne‐Sophie; McNeely, P. Daniel; Johnston, Donna; Lafay‐Cousin, Lucie; Wilson, Beverly; Eisenstat, David D.; Jabado, Nada; Zelcer, Shayna; Silva, Mariana; et al.
Abstract : BACKGROUND: The cure rate for childhood intracranial ependymoma is approximately 70% in the setting of a gross total resection followed by radiation, but management remains challenging in patients with residual disease. Therefore, robust biomarkers are needed to guide the development of new targeted therapy. The authors evaluated the expression of several biomarkers in pediatric intracranial ependymoma and observed that the expression of enhancer of zeste homolog 2 (EZH2), a polycomb complex protein involved in epigenetic regulation of gene expression, was independently associated with poor survival. METHODS: Tissue microarray immunostaining was performed on 180 ependymoma samples from 12 of 16 Canadian pediatric centers. Expression levels of EZH2, Ki‐67, B lymphoma Moloney‐murine leukemia virus insertion region 1 homolog, tumor protein 16 (P16), Y‐box binding protein 1, phosphorylated protein kinase B (pAKT), and epidermal growth factor receptor were evaluated. Cox regression analyses were performed, and the Kaplan‐Meier method was used to construct survival curves. RESULTS: EZH2 expressed in 16% of tumors was associated with inferior 5‐year overall survival. Ki‐67 and pAKT levels were associated with a poor outcome in patients with posterior fossa ependymoma, and the absence of P16 was associated with a poor outcome in patients with supratentorial ependymoma. Multivariate analysis revealed that younger age and EZH2 expression (95% confidence interval, 1.1‐36.0) were independent markers of a poor prognosis. CONCLUSIONS: EZH2 is a novel, independent marker of a poor prognosis in patients with ependymoma, especially in those who have tumors located in the posterior fossa. EZH2, pAKT, and P16 are potential therapeutic targets, particularly for patients who have tumors in which standard gross total resection plus fractionated radiotherapy is not feasible. Cancer 2015;121:1499–1507. © 2015 American Cancer Society . Abstract : Expression levels of several biomarkers are investigated in pediatric intracranial ependymomas, and enhancer of zeste homolog 2 (EZH2) expression is independently associated with poor survival. Thus, EZH2 is identified as a novel prognostic factor in pediatric intracranial ependymoma.